2016
DOI: 10.1093/eurheartj/ehv744
|View full text |Cite
|
Sign up to set email alerts
|

A head-to-head pharmacodynamic comparison of prasugrel vs. ticagrelor after switching from clopidogrel in patients with coronary artery disease: results of a prospective randomized study

Abstract: NCT01852175.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 28 publications
1
26
1
6
Order By: Relevance
“…Pharmacodynamic Comparisons Among Groups Comparison in platelet reactivity across time points among ticagrelor 180 mg loading dose (LD) group (Tic 180 mg), ticagrelor 90 mg bid maintenance dose (MD) without LD group (Tic 90 mg), and prasugrel 10 mg QD MD group (Pras 10 mg). Similar to other PD investigations, dyspnea occurred in approximately one-third of patients who switched to ticagrelor(11,12); however, this was mostly mild and transient and led to discontinuation of study drug only in 1 patient. The p values represent the comparisons among the 3 groups at each time point.…”
contrasting
confidence: 94%
“…Pharmacodynamic Comparisons Among Groups Comparison in platelet reactivity across time points among ticagrelor 180 mg loading dose (LD) group (Tic 180 mg), ticagrelor 90 mg bid maintenance dose (MD) without LD group (Tic 90 mg), and prasugrel 10 mg QD MD group (Pras 10 mg). Similar to other PD investigations, dyspnea occurred in approximately one-third of patients who switched to ticagrelor(11,12); however, this was mostly mild and transient and led to discontinuation of study drug only in 1 patient. The p values represent the comparisons among the 3 groups at each time point.…”
contrasting
confidence: 94%
“…Besides, Rollini and colleagues also found similar platelet aggregation values in patients with previous PCI (n = 110), who were switched from clopidogrel MD to either prasugrel or ticagrelor using light transmission aggregometry, the VerifyNow P2Y12 system, and the VASP assay [29]. Of note, in this study population HTPR rates on clopidogrel MD varied from only 13.6% to 66% depending on the assay used for platelet function testing [29], whereas in our study population, exclusively patients with HTPR on clopidogrel LD within the first hours after PCI were included.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, to what extent our findings can be extrapolated to ticagrelor remains unclear. Nevertheless, prasugrel and ticagrelor have very similar P2Y 12 inhibitory effects 38 and a randomised study comparing the two drugs in patients with acute coronary syndrome showed similar efficacy and safety outcomes. 10 This suggests that our findings could indeed apply to patients with acute coronary syndrome treated with ticagrelor.…”
Section: Hr (95% CImentioning
confidence: 97%